2020
DOI: 10.3390/agronomy10020188
|View full text |Cite
|
Sign up to set email alerts
|

Approach to Petiole Sap Nutritional Diagnosis Method by Empirical Model Based on Climatic and Growth Parameters

Abstract: The aim of this work is to evaluate the relationship between the nutrient concentration in petiole sap and different agronomic and climatic variables for a tomato crop grown in a greenhouse in Mediterranean conditions. In addition, the persistence of the nutrient concentration in petiole sap was investigated with the aim of determining the sampling period that implies the best trade-off nutritional information. The experiment consisted of the selection of 20 sampling points inside the greenhouse. The samples o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 23 publications
0
11
0
4
Order By: Relevance
“…Similar results were also noted by Abd El-Rheem et al [15] (P/N; 23.88%) and Sánchez et al [11] (Ca/N; 25.62%) in pepper crop. The importance of N/P in the FD can be due to the high mobility translocation of both elements from leaf to the most nutrient demanding organs (fruits) [32,33]. No references in the literature about the relationship between Ca and N nutrients were found, but it is necessary to mention that both elements are essential in yield pepper [30], especially Ca which is one of the most demanded nutrients in fruit development and any deficiency may result in loss of yield [34].…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were also noted by Abd El-Rheem et al [15] (P/N; 23.88%) and Sánchez et al [11] (Ca/N; 25.62%) in pepper crop. The importance of N/P in the FD can be due to the high mobility translocation of both elements from leaf to the most nutrient demanding organs (fruits) [32,33]. No references in the literature about the relationship between Ca and N nutrients were found, but it is necessary to mention that both elements are essential in yield pepper [30], especially Ca which is one of the most demanded nutrients in fruit development and any deficiency may result in loss of yield [34].…”
Section: Discussionmentioning
confidence: 99%
“…The concentration range of the NO 3 anion in soil solution was recorded in a variable range from 40 to 620 mg L -1 . Most changing values were recorded in the pepper crop, 220-620 mg L -1 during the floweringfruiting stage and 40-70 mg L -1 in the pre-harvest stage, which can be considered acceptable compared to the one found (396.8-1178 mg L -1 ) by Llanderal et al (2020) throughout the pepper crop cycle. Rodríguez et al (2020) propose a nitrate suff iciency value of 5 mmol L -1 (310 mg L -1 ) for soil-established pepper crops; however, this value only applies to vegetative growth.…”
Section: Resultsmentioning
confidence: 68%
“…However, statistically signif icant negative correlations were found in raspberry, cantaloupe, and pepper crops, suggesting that higher application rates do not reflect higher assimilations. About this, it has been found that the concentration of nutrients in the PCE is a function of the level of demand of ions for some physiological processes, such as nutrient uptake, bioassimilation, and storage (Llanderal et al, 2020), while decrease in ions in soil solution, generally is due to leaching towards lower depths, or to high assimilation by plants in certain phenological stages (Komosa et al, 2017). The foregoing supposes the occurrence of a negative correlation when high mineral applications are combined with periods of low plant demand.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The extraction of soil solution was done recurring to suction cups [38][39][40]. Soil water properties are given in Table 1.…”
Section: Methodsmentioning
confidence: 99%